Bifocal Presentation of Primary Testicular Extranasal NK/T-Cell Lymphoma: A Case Report and Review of the Literature. (12th August 2013) - Naboush, Ali; Farhat, Firas; Nasser, Selim M.; Kamar, Francois G.
Abstract : Introduction . Testicular lymphoma is an aggressive disease with a very poor prognosis. Nasal-type natural killer/T-cell lymphoma (NKTCL-N) in particular is very uncommon and has a rapidly progressive, fatal course. Case Report . We report a case of primary NKTCL-N of the testis in a 38-years-old Middle Eastern man. The patient had a history of primary right testicular tumor diagnosed at an outside institution as a seminoma and treated with orchiectomy followed by chemo/radiation. On admission, the patient had an enormous nasal granuloma with blood workup showing pancytopenia and elevated liver function tests due to active hepatitis B infection. CT scan of the sinuses showed a very large soft tissue mass, and PET scan showed splenomegaly with multiple lymph node masses in the pelvis and the chest areas. Bone marrow and nasal tumor biopsies as well as review of the slides from the initial orchiectomy were all in favor of NKTCL-N lymphoma. The patient was treated with CHOD based combination chemotherapy and responded dramatically to the first two cycles but passed away from fulminant hepatitis B infection. Conclusion . Despite all known treatments of NKTCL-N lymphoma of the testes, this disease has a very poor prognosis and invariably follows an aggressive clinical course.